1-Year development trend of concrete compressive strength using Calcium Sulfoaluminate cement blended with OPC, PFA and GGBS. (20th February 2019) - Yeung, Jaime S.K.; Yam, Michael C.H.; Wong, Y.L.
Abstract: In recent years, Calcium Sulfoaluminate Cement (CSAC) has become widely used in concrete repair works due to its outstanding properties of volume stability and rapid strength gain. Nevertheless, with the increasing concerns on cost and the embodied carbon of concrete, people start considering the possibility of blended combination of CSAC with less costly Ordinary Portland Cement (OPC) and more environmental friendly binder materials like Pulverized Fuel Ash (PFA) or Ground Granulated Blastfurnace Slag (GGBS). However, due to the completely different hydration process of CSAC comparing with OPC, reactions of CSAC with these binder materials have not yet been fully understood so far through systematic research, notwithstanding that numerous studies have been done on the strength development trend of concrete with OPC blended with PFA or GGBS. The objective of this research is to determine the long-term strength development trend of concrete using different combinations of CSAC with OPC, PFA & GGBS and to derive empirical equations for predicting early and later strengths of concretes with various binder combinations incorporating CSAC at different ages. A test regime consisting of totally 20 concrete mixes was conducted to examine the effect of different binder combinations on the concrete compressive strength at different ages from 2 h up to one year (365 days). The test results show that with the same total binder content, concrete mixes with increasing percentage content of CSAC exhibit increasing early strength. For concrete mixes with combination of CSAC with PFA or GGBS only, their concrete compressive strengths at later ages drop significantly when OPC is not present. This is believed to be the result of lacking of calcium hydroxide, which is the hydration product of OPC, to activate the hydraulic properties of PFA or GGBS to contribute in strength development. Nevertheless, it is found that a small quantity down to 5% of OPC is already adequate to bring the long-term strength at 365 days up to the same order as that of ordinary pure OPC concrete. Equations are derived for the prediction of strength performance of concrete with various binder combinations at different ages for the consideration of engineers at design or planning stage. Outcome of this research is able to give a picture for the strength development trends of concretes with different percentage combinations of CSAC with commonly used binder materials. The derived equations also give valuable information at the design stage for engineers to determine suitable percentage of different binder materials in concrete to be used giving a balance of benefits in the aspects of strength performance at early and long-term stages as well as economic and environmental considerations.